Evaluation of perforator flap for soft tissue reconstruction of distal leg and foot - Hemin Aladden Saeed; Madhar Ali Amin; Abdulrahman Baiz Abdulrahman (Advanced Medical Journal)
Background and objectives: Reconstruction of soft tissue defect of the distal leg and foot is regarded as a major task in plastic reconstructive surgery, durable coverage of such defect is usually needed. Using of local flap based on a single perforator raises interest for a reconstructive surgeon to reconstruct the leg. The aim of the study is to evaluate the versatility of the perforator flap for reconstruction of the soft tissue defect in the distal leg and foot according to: donor sit morbidity, flap viability and extent of coverage. Method: This is prospective study conducted in KRG (Kurdistan region government) of Iraq, twelve patient involved in this study, seven of them were males (n=7) and the other were females (n=5), and the mean age of 31 years (8-62), with soft-tissue defect, mean (5.8-14.5cm), defect where located in the distal leg in eleven patients and two located in the foot, all defects was due to road traffic accident treated with perforator flap (one patient both legs operated). Results: in this study, twelve patients were involved and thirteen procedures were done for them, in eight out of thirteen procedures the flap survived totally without complication 61.5%, in one patient flap is totally lost 7.7%, while in another developed complication in form of partial necrosis in three cases 23.1% and flap congestion in one case. Conclusion: The perforator flap is a reliable flap for soft tissue reconstruction of distal leg and foot and can replace free flap in our practice in selected cases.